The Influence of Brand Image, Price and Product Quality on Decisions to Purchase Bread at Ropi Bread Shops - Wahyudi, Wahyudi; Syahruddin, Achmad (Journal of Business Management and Economic Development, 2024)
The aim of this research is to determine the influence of Organizational Culture (X) on the Performance of Non-Permanent Employees (Y). The total number of respondents was 52 respondents. The analysis used in this research is simple regression analysis. The results of the validity coefficient for the 14 statement items are 14 valid items and 0 are invalid so it can be concluded that the 14 statement items are valid as a measuring tool because they have rcount > rtable, namely 0.2732. The results of the researcher's reliability variable calculations can be concluded that all statement items are reliable as measuring tools because the Cronbach's alpha value is 0.900 > 0.60. This simple linear regression can be explained as follows: A constant of 2.231 means that the performance of non-permanent employees at the Paser Regency Public Works and Spatial Planning Service will remain at 2.279 if (X) the cultural factor remains constant or there is no change. Based on the research results, it is known that the R value is 0.717 or 71.7%, this means that there is a strong relationship between the Organizational Culture variable (X) and the employee performance variable (Y), while the coefficient of determination is 0.514 or 51.4%, meaning the performance variable employees (Y) are explained by the organizational culture variable (X), amounting to 51.4% while the remaining 48.6% is explained by other variables not included in this research. From the t test results of the organizational culture factor (x), the calculated t value is 7.278 > t table of 2.00856, which means that the organizational culture factor (x) influences employee performance at the Paser Regency Public Works and Spatial Planning Service with a significant level of 0.000 < 0 .05. So it can be concluded that the hypothesis can be accepted or H0 is rejected and Ha is accepted, because the organizational culture factor (x) has a strong influence on employee performance at the Paser Regency Public Works and Spatial Planning Service.